Perancangan Sistem Monitoring Tegangan Baterai 110 VDC Berbasis Bylnk Pada Gardu Induk - Aripin Triyanto; Wahyu Syaepudin (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
Transmission equipment at 150 kV substations needs to be maintained for system reliability, especially equipment with a DC voltage supply because it plays an important role in 150 kV substations. DC source monitoring equipment is used to determine the value of the voltage flowing and the source that comes from the rectifier or battery. The problems encountered in this research are related to the voltage drop that occurs in the battery. The cause of damage to the battery is due to the reduced value of the input voltage and there is no supply voltage source. The solution to the problem is using hardware, making simulations using Blynk and NodeMCU software for battery conditions. The purpose of this study is to determine the value of the input voltage under undervoltage, normal and overvoltage conditions. The research results obtained on the use of a multimeter show that there is a difference of 0.3 Volts when undervoltage occurs. Software on the dashboard display made with notifications on the Blynk application if undervoltage occurs, namely the voltage is below 90 volts with email notifications and display on the Blynk application. Under normal conditions, the battery voltage is 126.9 Volts and there is no notification. During the overvoltage condition, the voltage is above 130 volts, causing the 110 VDC battery unit voltage monitoring equipment to send the result data from the measurements that have been installed on the 110 VDC battery unit fuse box to Blynk